Advances in Fiber‐Optic Technology for Point‐of‐Care Diagnosis and In Vivo Biosensing. Issue 5 (5th March 2020) - Tabassum, Shawana; Kumar, Ratnesh
Abstract: Development of reliable, sensitive, selective, and miniaturized sensing technologies is critical for health assessment and early diagnosis and treatment of diseases/anomalies while simultaneously mitigating the challenges associated with in vivo measurements. Some critical constraints to the realization of in vivo measurements include the necessity to fabricate the sensor on a tightly constrained footprint while ensuring acceptable biocompatibility, accuracy, and reliability. The inherent light‐guiding properties of optical fibers over long distances, their microscopic cross‐section that can be structured at the nanoscale to manipulate the light transmittance/reflectance spectrum, excellent biocompatibility enabling their efficient integration with biorecognition molecules, immunity to electromagnetic interference, mechanical flexibility, and low cost have been inviting research attention to utilize these unique features for in vivo and label‐free point‐of‐care diagnostics. Hence, fiber‐optic biosensing has become a promising research thrust, with a plethora of emerging methodologies to develop ultrasensitive and selective sensing probes. A unified presentation of the research trends on biosensors incorporated into optical fibers is presented. Abstract : The inherent light guiding properties of optical fibers over long distances, their microscopic cross‐section, excellent biocompatibility enabling their efficient integration with biorecognition molecules, mechanical flexibility, and low cost have invited research attention to utilize these unique features for in vivo and label‐free point‐of‐care diagnostics. A unified presentation of the research trends on reliable, sensitive, selective, and miniaturized biosensors incorporated into optical fibers is provided.